1991
DOI: 10.1161/01.hyp.18.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-free calcium and vascular calcium uptake in ethanol-induced hypertensive rats.

Abstract: This study examined the effect of moderate ethanol intake on systolic blood pressure, platelet cytosolic free calcium, aortic calcium, and rubidium-86 uptake in Wistar-Kyoto rats. Twelve Wistar-Kyoto rats, aged 6 weeks, were given 5% ethanol in drinking water the first week followed by 10% ethanol in drinking water for the next 6 weeks. Twelve control animals were given regular tap water. Systolic blood pressure in the ethanol-treated rats was significantly higher (p<0.05) than that in controls after 1 week an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Namely, a significant association between facial flushing response and the presence of ALDH2*2 allele was observed in 53 individuals, and in a subsequent large-scale study on 1000 or more individuals, drinkers manifesting the flushing response showed a higher prevalence of hypertension than those who did not. Itoh et al 5 thus speculated that people who have ALDH2*2 allele are more sensitive to the pressor effect of alcohol, and referred to the pathogenetic role of acetaldehyde in BP elevation in drinkers, which is consistent with the hypothesis proposed by Vasdev et al [6][7][8][9] from the results of studies on rats fed ethanol-water solution.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Namely, a significant association between facial flushing response and the presence of ALDH2*2 allele was observed in 53 individuals, and in a subsequent large-scale study on 1000 or more individuals, drinkers manifesting the flushing response showed a higher prevalence of hypertension than those who did not. Itoh et al 5 thus speculated that people who have ALDH2*2 allele are more sensitive to the pressor effect of alcohol, and referred to the pathogenetic role of acetaldehyde in BP elevation in drinkers, which is consistent with the hypothesis proposed by Vasdev et al [6][7][8][9] from the results of studies on rats fed ethanol-water solution.…”
Section: Introductionmentioning
confidence: 57%
“…The pathogenesis of alcohol-induced hypertension as related to acetaldehyde has been proposed by Vasdev et al from the findings in experiments on rats fed ethanol water solution, namely, parallel elevations in BP and cytosolic-free calcium concentration in the platelets, 6,7 and the prevention of those elevations by the administration of aldehyde absorbing substances. 8,9 Vasdev et al speculated that BP in drinkers is elevated due to increased vascular smooth muscle tonus owing to the higher intracellular calcium caused by the effect of acetaldehyde on the cell-membrane calcium exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the plasma level of norepinephrine was decreased in ethanol-fed animals. Vasdev et al 82 observed BP elevation after 1 week during the administration of ethanol (5-10%) to Wister Kyoto rats. They noted increases in the concentration of platelet intracellular calcium ions and the uptake of calcium in the aorta.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…It was demonstrated that intracellular Ca 2+ in a vascular smooth muscle cell preparation, even in the presence of Ca 2+ channel blockade, increases with ethanol (Vasdev et al, 1991). Ethanol has complex direct vascular effects, which include basal vasoconstriction and prominent elastic lamellae fragmentation which affects vessels elasticity (Estruch and Coca, 2004).…”
Section: Introductionmentioning
confidence: 99%